PENGARUH PROFITABILITAS, LIKUIDITAS DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN - WP, Bima Fikri Anggareksa; Ulupui, I Gusti Ketut Agung; Yusuf, Muhammad (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This study aims to examine the effect of profitability, liquidity, and solvency on the value of companies listed in the LQ45 index on the Indonesia Stock Exchange (IDX) during the period 2021-2023. This study uses secondary data obtained from the annual financial statements of LQ45 companies published on the IDX website (www.idx.co.id). The research sample consisted of 28 companies that were consistently listed in the LQ45 index during the period. The analysis method used is panel data regression analysis using Eviews 13 software. The results showed that profitability has a positive and significant effect on firm value, liquidity has no significant effect on firm value, and solvency has a positive and significant effect on firm value. This research has important implications for investors, company management, government, and the Indonesia Stock Exchange in decision making and policy formulation